Acute poisonings by drugs used for the treatment of cardiovascular diseases in the Republic of Serbia - Kovačević, Milica; Baralić, Katarina; Buha Djordjević, Aleksandra; Ćurčić, Marijana; Antonijević Miljaković, Evica; Bulat, Zorica; Antonijević, Biljana; Djukić-Ćosić, Danijela (Archives of Pharmacy, 2022)
Acute poisonings by drugs used for cardiovascular diseases treatment are less frequent than poisonings by other drugs, but often lead to serious disorders in various organ systems and are characterized by relatively high mortality. When it comes to polydrug poisoning by drugs with a depressant effect on the cardiovascular system, hospital care of the patients is necessary. This research aimed to present data on acute poisonings by drugs used in the cardiovascular diseases treatment in the Republic of Serbia in the period 2010-2018 based on the published Annual reports of the National Poison Control Center of the Military Medical Academy. Number of patients examined on suspicion of poisoning by drugs for cardiovascular diseases treatment, in the period 2010-2018, ranged from 4-6% of all examined due to acute drug poisoning per year, while number of hospitalizations due to drug poisoning ranged from 7 to 11% of all hospitalized patients. Of the total number of deaths resulting from drug poisoning, 27% are patients who died due to the poisoning by drugs used for cardiovascular diseases treatment. The most common causes of poisoning in the examined patients were beta blockers (45%), followed by Ca2+ channel blockers (25%) and ACE inhibitors (21%), and these three groups of drugs are the most common causes in hospitalized patients as well. Lethal outcomes are most often the result of acute poisoning by Ca2+ channel blockers (50%) and beta blockers (40%), mainly in combination with drugs used in psychiatric illnesses treatment, such as benzodiazepines, antiepileptics and antipsychotics.